2014
DOI: 10.1039/c4ra11239c
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids improve the anticorrosion performance of Zn-rich coatings

Abstract: In this work, the suitability of the ionic liquid 1-ethyl-3-methyl imidazolium ethylsulfate (C2C1imC2SO4) for improving the anticorrosive behaviour of zinc rich paints (ZRP) has been demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Among these strategies, ionic liquids (ILs) offer several promising properties that make them attractive electrolytes in improving the battery performance and extending the cell lifetime . Furthermore, hydrogen evolution and self‐discharge of the zinc anode can also be improved in IL electrolytes . We and others have previously studied the electrodeposition of zinc from ILs .…”
Section: Figurementioning
confidence: 99%
“…Among these strategies, ionic liquids (ILs) offer several promising properties that make them attractive electrolytes in improving the battery performance and extending the cell lifetime . Furthermore, hydrogen evolution and self‐discharge of the zinc anode can also be improved in IL electrolytes . We and others have previously studied the electrodeposition of zinc from ILs .…”
Section: Figurementioning
confidence: 99%
“…[9][10][11] Imidazolium ILs and their derivatives are one of the most effective and the most commonly used ILs as corrosion inhibitors in different corrosive media for carbon steel. [12][13][14][15][16][17] In addition, it was reported that quaternary ammonium, 18,19 phosphonium, 20 and pyridinium salts ILs 21,22 could be used for the protection of steel. Taghavikish et al 23 reported the improved anticorrosion ability for PILs based on thiol-ene derivatives.…”
Section: Introductionmentioning
confidence: 99%